2196. Effect of Depression, Anxiety, Stigma, and Disclosure on Quality of Life Among People Living with Hepatitis B Infection in Dalian, China. (26th November 2018) - Li, Ge; Wang, Gongchen; Hsu, Fang-Chi; Pei, Xia; Zhao, Bo; Xu, Jianzhao; Shetty, Avinash
Abstract: Background: In China, chronic hepatitis B virus (HBV) infection is a major public health problem with ~6% of the population chronically infected. We investigated the effect of depression, anxiety, stigma, and disclosure on health-related quality of life (HRQoL) among people living with chronic HBV infection (CHB) in Dalian city, Liaoning, China. Methods: Using a cross-sectional study design, 401 subjects with CHB were studied from January 2017 to September 2017. Study measures included Beck depression and anxiety inventory, WHOQOL-BREF, Toronto Chinese HBV Stigma Scale, and a questionnaire, which collected sociodemographic characteristic and disclosure of positive HIV status to sexual partners. The primary outcome was HRQoL score. A linear regression model examined the association between HRQoL and the potential risk factors including stigma, disclosure, depression, anxiety, and socio-demographic factors. Stigma, disclosure, depression, and anxiety are the covariates of interest. Age, sex, education, medical insurance, cirrhosis, other chronic diseases, and years of diagnose were adjusted in the model. Results: Majority of participants were males (251, 62.59%). married (37.41%), and completed high and middle school (67%). Four factors of Depression, anxiety, stigma and disclosure had negative associated with QOL physical, psychological, social and environmental domains ( P < 0.05) among CHB patients. Depression was the independent factor significant negative associated with HRQoL ( P < 0.0001). Patients' age had a significantly negative association with HRQOL in the psychological domain ( P = 0.0083). Patients"education level had a significantly positive association with HRQOL for all four domains. Conclusion: Our study is the first time to evaluate psychosocial factors affecting the HRQOL among people living with CHB in Dalian. Depression significantly affects the HRQOL among people living with CHB in Dalian, China warranting the urgent need for screening, early diagnosis, and implementation and integration of psychological interventions as part of routine care. Disclosures: All authors: No reported disclosures.